Stakeholders from diverse backgrounds make similar judgments about ecological condition and collapse in Mongolian rangelands. Issue 1 (26th November 2021) - Batpurev, Khorloo; Sinclair, Steve J.; Avirmed, Otgonsuren; Scroggie, Michael P.; Olson, Kirk; White, Matthew D.
Abstract: Complex socio‐ecological problems typically involve a variety of stakeholders, with viewpoints that may range between consensus and deep disagreement over values and judgments. Understanding this distribution of opinion is key to finding conservation solutions. We examine how stakeholders with widely different backgrounds vary in their judgments of rangeland degradation in Mongolia's Gobi Desert, where grazing intensity is a contested issue. We gathered the judgments of 92 stakeholders from a highly diverse group including: (i) nomadic pastoralists (herders), (ii) experts in botany, (iii) experts in wildlife ecology, and (iv) conservation policy practitioners. These stakeholders considered degradation in five ecosystems including Desert shrublands, Steppe, and Siberian Elm riparian woodlands, using written site descriptions in a workshop context. Each stakeholder considered degradation using two conceptual frameworks: the notion of "ecosystem collapse" described by the IUCN Red List of Ecosystems and the concept of ecological condition. We used generalized additive models (GAMs) to examine the relationship between vegetation attributes and stakeholder judgments of condition. Although individual stakeholder varied in their judgments, we found only relatively small systematic variations between different types of stakeholders. Similarly, we found the degree of specialization of experts had little effect on the condition score. We also used GAMs to examine the relationship between vegetation attributes and stakeholder judgments of collapse, finding little variation between groups. We also explored the threshold of overall vegetation cover where stakeholders are likely to shift their judgment from collapsed to not collapsed, and while differences between ecosystems were observed, we found consensus between the different stakeholder groups within each ecosystem. Our results suggest that, at least in the context of the Southern Mongolia, diverse stakeholder groups have convergent views in respect to ecological degradation.